Construction and Validation of a Nomogram Prediction Model for the Risk of Cefoperazone Sodium/Sulbactam Sodium-Related Coagulation Disorders - Min M; Zeng J; Zou M; Peng Y (Infection and Drug Resistance, 2025)
Mengjun Min,1,* Jing Zeng,1,* Mingyue Zou,1 Yingxian Peng2 1Department of Pharmacy, The Sixth Hospital of Wuhan, Affiliated Hospital of Jianghan University, Wuhan, People’s Republic of China; 2Department of Pharmacy, Hubei No. 3 People’s Hospital of Jianghan University, Wuhan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yingxian Peng, Hubei No. 3 People’s Hospital of Jianghan University, No. 26 Zhongshan Road, Qiaokou District, Wuhan, Hubei, 430033, People’s Republic of China, Email pyx0316@163.comObjective: To construct and validate a nomogram prediction model for the risk of cefoperazone sodium/sulbactam sodium (CPZ/SAM)-related coagulation disorders in hospitalized patients.Methods: Patients treated with CPZ/SAM from January 2022 to December 2024 were enrolled and divided into a coagulation disorder group and a control group based on the occurrence of coagulation disorders. Clinical data were collected to identify risk factors and construct a nomogram model, which was validated using the Hosmer-Lemeshow goodness-of-fit test, receiver operating characteristic (ROC) curve, decision curve analysis (DCA), and clinical impact curve.Results: A total of 439 patients were included, with 86 cases (19.59%) in the coagulation disorder group and 353 cases in the control group. Multivariate analysis identified malnutrition, recent bleeding history, prolonged treatment duration with CPZ/SAM, combination use with carbapenems, and elevated serum creatinine as independent risk factors. The constructed nomogram had an AUC of 0.845, demonstrating good calibration ability (χ²=2.312, P=0.891), providing moderate net benefit in predicting the incidence of coagulation disorders, with consistent agreement between predicted and actual probabilities.Conclusion: The nomogram model effectively identifies high-risk patients, indicating that attention should be paid to the risk of coagulation disorders in patients with the above risk factors during CPZ/SAM treatment.Keywords: cefoperazone sodium/sulbactam sodium, coagulation disorders, predictive model, nomogram, antimicrobial stewardship